Screening of the white margined sole, Synaptura marginata (Soleidae), as a candidate for aquaculture in South Africa - Thompson, Ernst Frederick (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2004)
The white margined sole Synaptura marginata (Soleidae) was isolated as the most likely candidate for flatfish aquaculture in South Africa. The aim of the study was to screen the sole as a candidate aquaculture species by way of a comprehensive study of its biology and life history strategy and to identify possible "bottlenecks". The study was undertaken on the assumption that the biological data would provide valuable information for developing specific technologies that might be required for the farming of this species. Specimens were collected monthly by spearing along the Eastern Cape coast of South Africa between December 2000 and March 2002. Length-at-age data required for modeling the growth of S. marginata was obtained from sectioned otoliths. A Von Bertalanffy growth model with an absolute error structure best describes the growth for this species. The model parameters were: Lâˆž = 429.5 mm TL, K = 0.24 and tâ‚€ = -1 .79 years. Analysis of gut contents showed that S. marginata feed exclusively on polychaete worms, mainly of the genus Morphysa. S. marginata shows a protracted summer spawning season of six months, from October to April. This was determined by the calculation of a monthly gonadosomatic index and a macroscopic maturity scale. Histological examination of the ovaries revealed five ovarian developmental stages. Size at 50% and 100% sexual maturity for females was calculated to be 235 mm TL and 300 mm TL (ca. 1.5 - 2.5 years of age) and all males> 154 mm TL were mature. S. marginata is a batch spawner, releasing a minimum of 3 batches of eggs per year. Relative fecundity is high (34000 eggs per year I kg) and this coupled with the protracted spawning season would make it possible to obtain adequate numbers of juveniles (for farming) for approximately five to six months of the year. Comparative analysis of the biological characteristics in relation to other soles farmed elsewhere in the world suggests that S. marginata is a suitable candidate for marine fish culture in South Africa.
Keywords: Flatfishes -- South Africa; Aquaculture -- South Africa; Soleidae -- South Africa; Soleidae